The thermodynamic dissociation constants of ambroxol, antazoline, naphazoline, oxymetazoline and ranitidine by the regression analysis of spectrophotometric data - Meloun, Milan; Syrový, Tomáš; Vrána, Aleš (Talanta, 2004)
The mixed dissociation constants of five drug acids-ambroxol, antazoline, naphazoline, oxymetazoline and ranitidine-at various ionic strengths I of range 0.01 and 1.0 and at temperatures of 25 and 37 degrees C were determined using SQUAD(84) regression analysis of the pH-spectrophotometric titration data. A proposed strategy of efficient experimentation in a protonation constants determination, followed by a computational strategy for the chemical model with a protonation constants determination, is presented on the protonation equilibria of ambroxol. The thermodynamic dissociation constant pK(a)(T) was estimated by non-linear regression of {pK(a), I} data at 25 and 37 degrees C: for ambroxol p K (a ,1)(T )=8.05 (6) and 8.25 (4), logbeta (21)(T )=11.67 (6) and 11.83 (8), for antazoline p K (a ,1)(T )=7.79 (2) and 7.83 (6), p K (a ,2)(T )=9.74 (3) and 9.55 (2), for naphazoline pK (a ,1)(T )=10.81 (1) and 10.63 (1), for oxymethazoline pK (a ,1)(T )=10.62 (2) and 10.77 (7), pK(a,2)(T)=12.03(3) and 11.82 (4) and for ranitidine p K (a ,1)(T )=1.89 (1) and 1.77 (1). Goodness-of-fit tests for various regression diagnostics enabled the reliability of the parameter estimates to be found.
Keywords: regresní analýza; Ambroxol; ambroxol; Oxymetazoline; oxymetazolin; Spectrophotometry; spektrofotometrie; Antazoline; Naphazoline; Ranitidine; Regression Analysis; antazolin; nafazolin; ranitidin